Electrification of road transportation with utility controlled charging: A case study for British Columbia with a 93% renewable electricity target. (1st November 2019) - Keller, Victor; English, Jeffrey; Fernandez, Julian; Wade, Cameron; Fowler, McKenzie; Scholtysik, Sven; Palmer-Wilson, Kevin; Donald, James; Robertson, Bryson; Wild, Peter; Crawford, Curran; Rowe, Andrew
Highlights: Abatement cost of electrification of road vehicle fleet range from 14 to 21 /tCO2e . Electricity cost is up to 9% higher in scenarios with transport electrification. Eliminating renewable target negates 60% of GHG benefits of transport electrification. Use of UCC in half of available fleet may decrease generation capacity needs by 7%. Abstract: To mitigate emissions from the electricity and transportation sectors, large scale deployment of renewable energy generators and battery electric vehicles are expected in the coming decades. However, adoption of these technologies may exacerbate issues related to mismatch of electricity supply and demand. In this study, we utilize a hybrid capacity expansion and dispatch model to quantify grid impacts of the conversion of the entire road vehicle fleet to electric vehicles by 2050. We examine impacts of policies, such as targeting a renewable energy penetration of 93%, using British Columbia as a case study. Scenarios making use of utility controlled charging of vehicles to balance supply and demand are further analyzed. Results show that although electrifying the entire road vehicle fleet will require generation capacity to increase by up to 60%, relative to a scenario without electrification, levelized cost of electricity only increases by 9% in the same scenario due to availability of low cost generation options such as wind and solar. We also find that a 93% renewable energy target leads to carbon abatement costs 30% lower than a scenario where this policy is removed. Further use of utility controlled charging reduces total system capacity up to 7%.